1999
DOI: 10.1016/s0014-5793(99)00128-3
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyatractyloside increases the effect of oleate on mitochondrial permeability transition

Abstract: Addition of a low concentration of carboxyatractyloside (0.075 W WM) renders mitochondria susceptible to the opening of the non-specific pore by 5 W WM oleate, in a cyclosporin A-sensitive fashion. Matrix Ca P+ efflux as well as collapse of the transmembrane potential reveal permeability transition. The effect of oleate is reached after the titration, by carboxyatractyloside, of 38 pmol of adenine nucleotide translocase per mg mitochondrial protein. We propose that permeability transition may result from an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…It is important to note that the effects obtained with NEM on the action of these inducers on pore opening present new information: (i) the NEM-induced inhibition of pore opening as induced by CAT and agaric acid, (ii) the fact that ANT's function is inhibited by CAT and agaric acid without opening of the non-specific pore, (iii) the stimulating effect by NEM on oleate-induced permeability transition, and (iv) the increased binding of EMA to the ADP/ATP carrier after the addition of oleate. The fact that NEM inhibited the effect of CAT on Ca 2+ efflux and mitochondrial swelling cannot be explained considering the argument that NEM inhibits the binding of CAT, as has been proposed [7,18]. This assumption emerges from the finding that carboxyatractyloside still inhibits ADP Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is important to note that the effects obtained with NEM on the action of these inducers on pore opening present new information: (i) the NEM-induced inhibition of pore opening as induced by CAT and agaric acid, (ii) the fact that ANT's function is inhibited by CAT and agaric acid without opening of the non-specific pore, (iii) the stimulating effect by NEM on oleate-induced permeability transition, and (iv) the increased binding of EMA to the ADP/ATP carrier after the addition of oleate. The fact that NEM inhibited the effect of CAT on Ca 2+ efflux and mitochondrial swelling cannot be explained considering the argument that NEM inhibits the binding of CAT, as has been proposed [7,18]. This assumption emerges from the finding that carboxyatractyloside still inhibits ADP Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In turn, Mironova et al [17] showed that palmitic and steraric acids induce non-specific ion channels in black-lipid membranes. It has also been reported that oleate induces permeability transition, through a mechanism that is inhibited by cyclosporin A [18].…”
Section: Introductionmentioning
confidence: 95%
“…ANT forms the PT pore when associated with cyclophilin-D in the mitochondrial matrix and the nonselective voltage-dependent anion channel in the mitochondrial outer membrane (voltage-dependent anion channel is located at the contact points between the inner membrane cristae and the outer membrane). Cyclosporin-A (a ligand of with cyclophilin-D) and some inhibitors of the ANT inhibit PT pore formation, whereas other ANT inhibitors increase the probability of pore opening (Zamzami et al, 1996;Chavez et al, 1999).…”
Section: Mechanism Of Action Of Clodronate 1259mentioning
confidence: 99%
“…The effect of ANT inhibition on PT pore formation depends on whether the ligands bind to the m-state or c-state. Ligands binding to the m-state inhibit the formation of the PT pore and ligands binding to the c-state induce the formation of the PT pore (Zamzami et al, 1996;Chavez et al, 1999). If AppCCl 2 p acts as an enhancer of PT pore formation, it would be expected to do this by acting as a ligand binding to the c-state of the ANT (i.e., acting on the cytosolic side of the mitochondrial membrane).…”
Section: Mechanism Of Action Of Clodronate 1259mentioning
confidence: 99%
“…Recent reports have demonstrated, that FFA stimulate large‐amplitude swelling of mitochondria, preloaded with Ca 2+ and suspended in neutral medium (pH 7.2–7.4), by the opening of the permeability transition pore complex (PTP) [20–28]. In the present paper we studied large‐amplitude swelling initiated in mitochondria by Myr in alkaline KCl medium.…”
Section: Discussionmentioning
confidence: 91%